The Relationship between Sociodemography and the Level of Knowledge, Attitudes, and Behavior of Breast Cancer Patients at the Surgical Oncology Polyclinic at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia - Raden Yohana; Rani Septrina; Adi Setiawan Suryadi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Breast carcinoma is the most frequently diagnosed carcinoma in the world. A person's behavior in responding to a health problem is influenced by three factors, namely predisposing factors, supporting factors, and needs factors. The predisposing factor explaining social demographics is one of the things that influence individuals to overcome health problems. This study aimed to assess the level of knowledge, attitudes, and behavior toward breast cancer in advanced breast cancer patients who seek treatment at the surgical oncology polyclinic at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia. Methods: This study was an analytic observational study of 329 research subjects. The research subjects were patients at the surgical oncology polyclinic at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia. Observation of knowledge, attitudes, and behavior was carried out using a questionnaire adapted from the breast cancer awareness scale (BCAS-I). Data analysis was performed univariate, bivariate, and multivariate using SPSS software. Results: Occupation (p-value 0.000 OR 3.664) has a significant relationship with the knowledge of breast cancer patients. Education and occupation have a significant relationship with the attitude of breast cancer patients. Age 35-59 years and working as a housewife have a significant relationship to the behavior of breast cancer patients. Conclusion: There is a sociodemographic relationship with knowledge, attitudes, and behavior in breast cancer patients at the surgical oncology polyclinic at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia.